2
$\begingroup$

I understand that $$ \lim_{n\rightarrow \infty} \left(1 + \frac{1}{n}\right)^n = e $$

However, how would $ \lim_{n\rightarrow \infty} \left(1 + \frac{1}{3n}\right)^{5n} $ be simplified.

The $5$ can be moved outside the limit:

$$ {\lim_{n\rightarrow \infty} \left[\left(1 + \frac{1}{3n}\right)^{n}\right]^5} $$

But how can you simplify it to the form $e^{\frac{m}{n}}$?

The answer is $ e^{\frac{5}{3}} $, but could someone help me understand the methodology?

$\endgroup$
  • 6
    $\begingroup$ $\left\{\left(1+\frac{1}{3n}\right)^{3n}\right\}_{n\geq 1}$ is a subsequence of $\left\{\left(1+\frac{1}{n}\right)^{n}\right\}_{n\geq 1}$, hence it converges to the same limit, $e$. Given the continuity of $x\mapsto x^{5/3}$ over $\mathbb{R}^+$, your limit equals $e^{5/3}$. $\endgroup$ – Jack D'Aurizio Sep 3 '18 at 19:05
12
$\begingroup$

Don't move $5$. Move $5/3$ instead: $$\lim_{n\rightarrow \infty} (1 + \frac{1}{3n})^{5n}=\left(\lim_{n\rightarrow \infty} (1 + \frac{1}{3n})^{3n}\right)^{5/3}.$$ You will find the inside limit is $e$.

$\endgroup$
6
$\begingroup$

$\lim_{n\rightarrow \infty} (1 + \frac{1}{3n})^{5n} =\lim_{n\rightarrow \infty} ((1 + \frac{1}{3n})^{3n})^{5/3}= e^{5/3}$

$\endgroup$
3
$\begingroup$

Everybody has given the solution, but this is how it hit me,

$$\lim_{n\to \infty}\biggr(\bigg(1+\frac{1}{3n}\bigg)^n\biggr)^5$$

Let $$3n=t$$

$$\lim_{t\to \infty}\biggr(\bigg(1+\frac{1}{t}\bigg)^{\frac{t}{3}}\biggr)^5$$

$$\lim_{t\to \infty}\biggr(\bigg(1+\frac{1}{t}\bigg)^t\biggr)^\frac{5}{3}$$

$$e^\frac{5}{3}$$

$\endgroup$
0
$\begingroup$

As an alternative

$$\left(1 + \frac{1}{3n}\right)^{5n}=e^{5n\log \left(1 + \frac{1}{3n}\right)}\to e^{5/3}$$

indeed

$$5n\log \left(1 + \frac{1}{3n}\right)=\frac53\cdot\frac{\log \left(1 + \frac{1}{3n}\right)}{\frac1{3n}}\to\frac53 \cdot 1 = \frac53$$

$\endgroup$
0
$\begingroup$

Consider the most general case of $$y=\left(1 + \frac{1}{an}\right)^{bn}$$ Take logarithms $$\log(y)=bn\log\left(1 + \frac{1}{an}\right)$$ Now, use Taylor series $$\log(y)=bn\left(\frac{1}{a n}-\frac{1}{2 a^2 n^2}+O\left(\frac{1}{n^3}\right) \right)=\frac{b}{a}-\frac{b}{2 a^2 n}+O\left(\frac{1}{n^2}\right)$$ Use again Taylor $$y=e^{\log(y)}=e^{\frac{b}{a}}-\frac{b e^{\frac{b}{a}}}{2 a^2 n}+O\left(\frac{1}{n^2}\right)$$ which shows the limit and also how it is approached.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.